Taʻāwun dan Tradisi Pemotongan Lembu pada Peristiwa Kematian: Dialog Tafsir al-Misbah dan Tafsir Ibn Kaṡīr atas Surah al-Mā’idah Ayat 2 - Ummi Kalsum Nasution; Achyar Zein; Ernawati Beru Ginting (Yayasan Albahriah Jamiah Indonesia, 2026)
The practice of slaughtering cattle in the event of death in some Muslim communities raises normative tensions when confronted with the concept of taʻāwun in Surah al-Mā’idah: 2, which emphasizes cooperation in virtue and piety. This phenomenon shows the ambiguity between social solidarity and the potential shift in the value of worship into a socio-economic burden that causes problems. The study focuses on the interpretive dialogue between Tafsir Ibn Kaṡīr and Tafsir al-Misbah to examine the construction of the meaning of taʻāwun and its relevance in assessing the social practice of death. A qualitative approach based on literature studies is used, with a comparative analysis of the interpretations of both commentators, accompanied by a contextual reading of social reality. The results of the analysis show differences in epistemological orientation; Ibn Kaṡīr emphasizes the normative-textual dimension by affirming the boundary between virtue and practices that have the potential to lead to bidʻah, while Quraish Shihab offers a contextual reading with an emphasis on the value of benefit, social empathy, and the rationality of practice. The main findings indicate that taʻāwun is not merely symbolic cooperation, but rather an ethical principle that requires proportionality, non-burdensomeness, and alignment with the objectives of sharia. Theoretical implications point to strengthening an integrative approach to social interpretation. In contrast, practical implications emphasize the need to reconstruct traditions to align with collective virtues without creating socio-economic pressure on society.